Mentoring impact on the transversal competence’s development. An experience of educational accompaniment in the integral formation of the university student - Crespí, Paula; López, Jorge (Frontiers in Education, 2023)
The adaptation of universities to the new guidelines set by the European Higher Education Area implies relevant changes. Among them, a teaching model more focused on the student and his or her learning than on the teacher and the subject, new active teaching-learning methodologies and the development of competences through the acquisition of learning outcomes; all with the aim of contributing to the integral formation of the university student. The integral formation, enabling each student to discover and realize their own life project, is nourished by educational accompaniment and the development of competences. A concrete form of educational accompaniment is mentoring. The objective of this study is to evaluate the formative effectiveness of an innovative mentoring program in the development of transversal competences as a means to achieve the ultimate mission of the university: to provide a comprehensive education to students. The design of this research is quasiexperimental (pretest-posttest). The sample consists of more than 300 first-year students of the Universidad Francisco de Vitoria who participated in the mentoring program. A questionnaire on transversal competences and group interviews were used as measurement instruments. The results showed significant differences in the level of acquisition of intrapersonal competences between the pre-treatment and post-treatment periods, in favor of the latter. This fact suggests that students improved their level of intrapersonal competences thanks to the mentoring program. These results are subsequently supported by the analysis of the group interviews. Therefore, it can be concluded that this type of mentoring program is a valid example for the development of intrapersonal competences, which in turn contributes to the integral formation of the student.